Harmonia axyridis Does Not Have Obvious Fitness Gain and Preference to the Red Morph of Acyrthosiphon pisum: A Case Study on a Laboratory Strain - Sun, Yuan-Xing; Liu, Tong-Xian (Frontiers in Ecology and Evolution, 2018)
Prey selection was assumed to be a vital strategy to maximize the fitness of predators. Visual cues are important for predators to locate a prey, and several species of lady beetles prefer the red morph Acyrthosiphon pisum rather than the green morph in empty containers with different colors. However, the preference of a predator on different color morphs of prey on green plant leaves and the relationship between the fitness of the predator that feeds on the red and green color morphs of A. pisum have not been revealed. In this study, two colonies of the multicolored Asian lady beetle, Harmonia axyridis, a generalist predator, fed on a red morph and a green morph of A. pisum (indicated as RA-Har and GA-Har, respectively) were used to determine their prey preferences on the two morphs of A. pisum on leaf discs. The fourth instars and newly emerged adults of H. axyridis that fed on the two aphid morphs did not show any significant prey preference, except that GA-Har males consumed significantly more green morph than red morph. The fitness of RA-Har and GA-Har, including larval development and body weights of the fourth instars and the newly emerged female adults were not significantly different, and so were the predation capability and fecundity. However, RA-Har had significantly higher larval hatch rate than GA-Har, and tended to produce more eggs on cage walls or plant pots than on broad bean leaves in the cage assays. Our results provide evidences that H. axyridis did not prefer either morph of A. pisum, and also did not show significant effect on fitness. We hope that results from this study will stimulate more studies to reveal the mechanism of colored prey preference of predators.